Exploring Students’ Strategies for Managing Speaking Anxiety at the Mathematics Department of Bima International MFH (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to identify the factors that cause speaking anxiety in students and the strategies used by students to reduce this anxiety. The focus of the study is on the experiences and strategies developed by students in dealing with speaking anxiety in the classroom. This study uses a qualitative descriptive approach with 16 first-semester students at Bima International University MFH as research subjects. Data collection was conducted through observation, in-depth interviews, and field notes. The results show that students' speaking anxiety is influenced by several main factors, namely fear of making mistakes, limited language exposure, and language competency gaps. These factors encourage students to develop various strategies to reduce speaking anxiety, including preparing before speaking, applying relaxation techniques, building positive mindsets, and seeking support from peers. These findings indicate that personal and social strategies play an important role in helping students manage speaking anxiety in the learning environment.